Strategi Segmentasi Pendengar Stasiun Jaringan Oz Radio di Era Digital - Aziiz, Abdul; Shabana, Amin (Educationist: Journal of Educational and Cultural Studies, 2023)
The aim of this research is to define problems such as geographic listener segmentation, demographic listener segmentation, psychographic listener segmentation and behavioral listener segmentation. The theory used in this research is Kotler's theory of listener segmentation strategies (Warter Gustim 2015). This research uses a qualitative approach with descriptive methods. The data produced in this research is in the form of interviews, field observations, documentation and other supporting documents. Oz Radio focuses on listeners in the Jabodetabek and South Jakarta areas in geographic segmentation, with the aim of accommodating local preferences and building strong connections with listeners. In demographic segmentation, Oz Radio targets ages 20 to 40-50 years in Jabodetabek and ages 18 to 35 years in Jakarta, with a focus on young people. In a behavioral segmentation strategy, Oz Radio attracts listeners with an interest in sidestream music and unique listening experiences. This overall segmentation strategy allows Oz Radio to build relevant and meaningful relationships with various listener segmentations in the ever-evolving digital era.